P12 Associations of aortic stenosis with factors relating to pregnancy in a cohort of 1.2 million UK women. (13th September 2016) - Cairns, BJ; Canoy, D; Reeves, GK; Green, J; Beral, V; ,
Abstract : Background: There are limited epidemiological data on risk factors for aortic valve stenosis, although it is known to share some features of its pathogenesis with coronary artery disease. Some reproductive factors relating to pregnancy have been found to be associated with coronary artery disease. The objective of this study was to investigate associations of risk of aortic stenosis with factors relating to pregnancy. Methods: At recruitment (study baseline), participants in a cohort of 1.2 million UK women reported information on a range of health and lifestyle factors, including their reproductive history. Data on hospital discharge diagnoses, as well as from death registries, were used to define incident aortic stenosis. We used Cox regression, adjusted for known behavioural and other personal risk factors for cardiovascular disease, to obtain estimates of the multivariable adjusted relative risk (RR) of AS, in association with five factors relating to pregnancy: age at menarche, past use of oral contraceptives, age at first birth, parity, and any history of hypertension in pregnancy. Results: Women were 56 (SD 6) years of age on average at study baseline. There were 4141 incident aortic stenosis events over an average of 11.9 years of follow-up. In preliminary multivariable analyses, there was no association of aortic stenosis with past use of oral contraceptives, age at first birth, or parity (likelihood ratio P > 0.3 for all comparisons). Allowing for multiple comparisons, there was some evidence of an association of aortic stenosis with age at menarche (P < 0.01), but the risk was only marginally elevated (RR = 1.1 for <13 years versus the median of 13 years). There was strong evidence that any history of hypertension in pregnancy was associated with a higher risk of aortic stenosis (RR = 1.5; P < 0.0001); this association was attenuated, but remained significant, after further adjustment for reported treatment for hypertension at baseline. Further follow-up data will soon become available, and updated results will be presented. Conclusion: Younger age at menarche may be associated with a small increased risk of aortic stenosis, but there was no association with age at first birth, parity, or past use of oral contraceptives. Hypertension diagnosed during pregnancy is a marker of the risk of hypertension in later life. The association between hypertension in pregnancy and aortic stenosis diagnosed decades later may be mediated, in part, by hypertension in later life.